Análisis de las Reformas Tributarias y su incidencia en el Impuesto a la Renta de la zona de planificación 7 de Ecuador, periodo 2019-2022 - García Salazar, Susana Elizabeth (2023)
The tax collection is crucial for a country as it constitutes part of the State’s financing. This research aims to analyze the impact of tax reforms instituted on income tax collection in the planning zones of Ecuador during the period 2019-2022, particularly in Zone 7, using a qualitative-quantitative approach. The research results reflect that the newly established simplified regimes provided benefits to taxpayers in terms of reducing the number of formal duties and facilitating compliance with tax obligations. However, it contradicted tax principles of fairness, progressivity, and contributory capacity, leading to inequity and discrimination in income tax calculations. It was also observed that in 2020 and 2021, tax collection decreased, while in 2022, there was a 72% increase. Furthermore, the province that contributed predominantly to income tax was El Oro, especially in 2019, 2020, and 2021, while in 2022, the province of Zamora Chinchipe took the lead. In conclusion, the impact of the reforms on income tax collection may be affected not only by new fiscal reforms but also by external factors such as tax evasion, political and economic instability, and high administrative costs to fulfill tax obligations, which can directly contribute to a decrease in tax collection.